An investigation into the selective separation and adsorption mechanism of a macromolecular depressant in the galena-chalcopyrite system. (April 2019) - Zhang, X.R.; Zhu, Y.G.; Zheng, G.B.; Han, L.; McFadzean, B.; Qian, Z.B.; Piao, Y.C.; O'Connor, Cyril
Graphical abstract: Highlights: PAM-ATU is synthesized by solvent method and innovatively used as galena depressant. PAM-ATU shows excellent depressing performance for galena at pH 8.0–9.0. Adsorption mechanism of PAM-ATU is investigated by FT-IR, Zeta potential and XPS. The adsorption model of PAM-ATU on galena surface is proposed. Abstract: In the present article, a macromolecular polymer poly(acrylamide-allylthiourea) (PAM-ATU) was synthesized by solvent method with an average molecular weight of 1.66 × 10 4 g/mol measured by GPC. Its structure was characterized by FT-IR, 1 H NMR and 13 C NMR. PAM-ATU was used as a selective galena depressant in the flotation separation from chalcopyrite. Its flotation depressing behavior and adsorption mechanism to galena were investigated by micro-flotation, FT-IR, zeta potential, adsorption tests and X-ray Photoelectron Spectroscopy (XPS). The micro-flotation experimental results for artificially mixed minerals demonstrated that PAM-ATU was an effective depressant for galena in the separation from chalcopyrite, depressing 90.91% galena with a grade of 79.93% at pH 8.0–9.0 with 1.0 mg/L dosage. Adsorption tests showed that PAM-ATU could strongly prevent IPETC collector adsorbing onto the galena surface. However, there was no obvious influence on chalcopyrite at pH 8.0–9.0. The FT-IR spectra, zeta potential and XPS analysis demonstrated that PAM-ATU might mainly chemisorb on galena surface by SPb bonds. Based on this research, the adsorption model of PAM-ATU onto galena surface was proposed.